Identifikasi Faktor Risiko Ergonomi pada Karyawan Minimarket di Denpasar - I Gusti Agung Ayu Dwitya Asrinda Socha; Ni Wayan Rusni; Ni Wayan Winianti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Minimarket employees are one of the examples of human labor who work manually and thus it often creates ergonomic problems that tend to have risks. The awkward work posture of minimarket employees can cause muscle and bone disorders or commonly referred to as musculoskeletal disorders. This condition can trigger the occurrence of impaired concentration and fatigue at work. This study aims to assess the ergonomic risk factors of minimarket employees in Denpasar. It includes awkward work posture, duration of work, forceful motion, and MSDs. The design used was descriptive study and a cross sectional approach. This study was done in several minimarkets in West Denpasar and South Denpasar for 4 months from March until June 2022. The samples used were minimarket employees in West Denpasar and South Denpasar based on predetermined criteria with a sampling technique of purposive sampling. This study was conducted among 96 employees of mini markets at West and South Denpasar. Data was obtained by filling out online questionnaires and interviews and then analyzed univariately. The results shows that 50 % of the minimarket employees in Denpasar had low risk work posture. About 68.8 % of the minimarket employed in Denpasar had complaints of musculoskeletal disorders in the low category, while 67.7 % of them experienced work exhaustion in the low category.